Możliwości wykorzystania systemu ADONISrisk do minimalizacji ryzyka operacyjnego w bankach spółdzielczych - Garczyński, Dariusz (Application of ADONISrisk system in operational risk minimalization in community banks, 2006)
The paper presents concepts of operational risk management under Basel II requirements and application of the system ADONISrisk for measuring and controling this kind of risk. Quantitative methods were presented with the stress on methods proposed by Basel II - BIA, SA and AMA. Due to the high needs of financial data it is not possible for small and medium banks like community banks to adopt such methods in nearest future, therefore some other solution must be applied. The workflow management system ADONIS with its component for risk management may be one of such tools.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 35-42